(untitled) (The Research of Medical Science Review, 2025)
Background: Mycobacterium Tuberculosis is a globally serious problem of health. While Culture takes too much time consuming and smear of microscopy gives us false negative and false positive results. ICT kit also give false positive results. GeneXpert MTB/RIF is a dependable program that is crisp and exact to an incredible degree. This study's primary objective is to determine whether or not the GeneXpert MTB/RIF is extremely trustworthy and capable of doing accurate job. Objective: To determine the early diagnosis suspected patients with tuberculosis using GeneXpert MTB/RIF assay in THQ Hospital Kot Radha Kishen. Methodology: This study was conducted in THQ Hospital. There collected respectively 120 suspected pulmonary tuberculosis patients (PTB) using GeneXpert MTB/RIF machine four module at a time run four samples which give highly precise results. Out of 120 how many suspected patients were detected MTB and analysis its results separately compared with Rifampicin Resistance antibiotic. Results: In results 17.5% (21/120) suspected patients were detected MTB while 3.3% (4/120) was detected Rifampicin Resistance indeterminate using GeneXpert MTB/RIF. Suspected patients of PTB were detected MTB 2.5% high, 10.8% low, 3.3% trace and 0.8% medium Conclusion: The Four modules GeneXpert method has high sensing efficiency. It has excellent indicate the value of infection and detecting of RIF and MTB, instead of in culture media and sputum smear formation results are negative and sometime interprets false positive results and important reduces the rate of false interprets. The diagnosed method of MTB using culture technique take days not done in hours.